VP Shunt Complications: Ten Years Experience at UDMNINAS - Lohani, Subash; Baniya, Aashish (Nepal Journal of Neuroscience, 2019)
Ventriculo-Peritoneal shunt is significantly associated with complications like malfunction and infection. In this study, we aim to review our infection and malfunction rate. This is a retrospective review of charts of patients who underwent ventriculo-peritonealshunt at Upendra Devkota Memorial National Institute of Neurological and Allied Sciences, Bansbari, Nepal between 2008 and 2018. Patients were interviewed via telephone for information regarding shunt complications in the form of malfunction, infection, and the need for revision. A total of 357 patients underwent ventriculoperitonealshunt over a period of 10 years. of patients was 37.08 years. There were224 males and133 females with M:F::1.7:1.265 patients were available over telephone for interview. 54 of 265 (20.37%) patients needed shunt revision. 32 (12.07%) of them had shunt malfunction. 21 (7.92%) of them had shunt infection. One (0.37%) patient had problems with over drainage. Shunt complications were proportionate in pediatric population as well. Shunt complication at Upendra Devkota Memorial National Institute of Neurological and Allied Sciences is comparable to international data.